CRISIS OF DEMOCRACY, POLITICAL DISTRUST AND AFRO-PESSIMISM IN NIGERIA POLITICS; THE FOURTH REPUBLIC IN FOCUS - LAMBE EMMANUEL OYEWOLE (International Studies Journal)
Democracy is highly celebrated as the best system for governance. The introduction of democracy into African society which in time replaced the old African political system, however even after political independence majority of African society continued with this same western political system which was seem as been more advance in providing equal opportunity, collective responsibility, human rights advancement, state development etc. However, there have been a repression, backsliding and crisis in the democracy of some states. Crisis of democracy are the threats to democratic principles. Huntington (1975) sees it as the excesses of government rule and citizenry repressions. Poor governance and "bad" politics in African countries as the personalized nature of rule, the failure of the state to advance and protect human rights, the tendency of individuals to withdraw from politics, and the extreme centralization of power in the hands of few people are the basis of the crisis of politics. The crisis in democracy has therefore expounded distrust, pessimism and skeptical relationship between the political elite and the citizenry. The research applies the quantitative research methodology. Further, the constructive theory of idea was employed to show the relationship between the crisis of democracy, distrust and afro-pessimism. More, the research found out that the historical trend of corruption, political repression, maladministration, political and ethnic crisis etc. are the factors mitigating against democracy. The research thereforerecommends that succinct and apt application of democratic principles and the end to political and administrative corruption is the major way out for solving Nigeria’s crisis of democracy.